Releasing the concept of HLA‐allele specific peptide anchors in viral infections: A non‐canonical naturally presented human cytomegalovirus‐derived HLA‐A*24:02 restricted peptide drives exquisite immunogenicity. (14th April 2019) - Pump, Wiebke C.; Schulz, Rebecca; Huyton, Trevor; Kunze‐Schumacher, Heike; Martens, Jörg; Hò, Gia‐Gia T.; Blasczyk, Rainer; Bade‐Doeding, Christina
Abstract : T‐cell receptors possess the unique ability to survey and respond to their permanently modified ligands, self HLA‐I molecules bound to non‐self peptides of various origin. This highly specific immune function is impaired following hematopoietic stem cell transplantation (HSCT) for a timespan of several months needed for the maturation of T‐cells. Especially, the progression of HCMV disease in immunocompromised patients induces life‐threatening situations. Therefore, the need for a new immune system that delivers vital and potent CD8+ T‐cells carrying TCRs that recognize even one human cytomegalovirus (HCMV) peptide/HLA molecule and clear the viral infection long term becomes obvious. The transcription and translation of HCMV proteins in the lytic cycle is a precisely regulated cascade of processes, therefore, it is a highly sensitive challenge to adjust the exact time point of HCMV‐peptide recruitment over self‐peptides. We utilized soluble HLA technology in HCMV‐infected fibroblasts and sequenced naturally sHLA‐A*24:02 presented HCMV‐derived peptides. One peptide of 14 AAs length derived from the IE2 antigen induced the strongest T‐cell responses; this peptide can be detected with a low ranking score in general peptide prediction databanks. These results highlight the need for elaborate and HLA‐allele specific peptide selection.